Stock Market Cycles and Supply Side Dynamics: Two Worlds, One Vision? - Paul De Grauwe; Eddie Gerba (Center for Economic Studies and ifo Institute (CESifo), 2015)
The paper compares two state-of-art but very dinstinct methods used in macroeconomics: rational-expectations DSGE and bounded rationality behavioural models. Both models are extended to include a financial friction on the supply side.The result in both models is that production, supply of credit and the front payment to capital producers depend heavily on the stock market cycles. During phases of optimism, credit is abundant, access to production capital is easy, the cash-in-advance constraint is lax, the risks are undervalued, and production is booming. But upon reversal in market sentiment, the contraction in all these parameters is deeper and asymmetric. This is even more evident in the behavioural model, where cognitive limitations of economic agents result in exacerbation of the contraction. While both models capture the empirical regularities very well, the validation exercise is even more favourable to the behavioural model.
Keywords: B41; C63; C68; E22; E23; E37; 330; supply-side; beliefs; financial frictions; model validations